Pengaruh Profitabilitas, Leverage, dan Likuiditas terhadap Agresivitas Pajak (Studi Empiris Perusahaan Sektor Energi yang terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Matanari, Dodi Antono (Jurnal Buana Akuntansi, 2022)
Taxation is one of the most important sources of funding for the development of facilities and infrastructure in any country. In Indonesia, the government has formulated various tax policies and regulations to maximize the income of the taxation department, because taxation can have a very large impact on government revenues and APBN budgeting. This of course requires companies to carry out tax aggressiveness, such as doing many ways in order to minimize tax payments. This study aims to examine the effect, profitability, leverage, and liquidity on tax aggressiveness in energy sector companies listed on the Indonesia Stock Exchange in 2018-2020. Research data is secondary data in the form of financial reports from companies. While the population in this study are all energy sector companies listed on the Indonesia Stock Exchange in 2018-2020. Sampling in this study using purposive sampling method where the total population is 72 companies. In accordance with the criteria of the selected sample, the sample companies in this study were 24 companies. The data analysis used in this research is multiple linear regression. The results of this study indicate that Profitability, Leverage and Liquidity have no effect simultaneously on tax aggressiveness, Profitability does not affect tax aggressiveness, Leverage does not affect tax aggressiveness, Liquidity does not affect tax aggressiveness.